(untitled) (Biodiversitas Journal of Biological Diversity, 2014)
Sanjay-Gandhi D, Sundarapandian S. 2014. Inventory of trees in tropical dry deciduous forests of Tiruvannamalai district, Tamil Nadu, India. Biodiversitas 15: 169-179. Diversity and distribution patterns of tree species were inventoried in 20 one hectare plots in Sathanur Reserve Forest of Tiruvannamalai district, Tamil Nadu, India. These plots were grouped into three sites based on their location in the reserve forest and the level of disturbance. Site I (8 plots) near to the road and agricultural lands, Site II (8 plots) away from the road and human settlements and site III (4 plots) along the canal-side where the terrain contain rocks here and there. A total of 60 species belonging to 48 genera and 29 families were enumerated including 13,412 stems (â‰¥3.2cm DBH size class). The species richness in the stand (plot) varied from 7 ha-1 to 28 ha-1 and the stand density varied from 336 ha-1 to 1075 ha-1. Albizia amara (7999) was the dominant species in terms of density, basal area and IVI in all the study plots except plot no.16, where Chloroxylon swietenia was dominant indicates a mono-species dominated forest ecosystem. The mean values of Shannon and dominance indices were 1.406 and 0.411 respectively. Diameter class-wise distribution showed L-shaped curve, a sign of good regeneration status. Cattle grazing and illegal fuel wood collection have been observed to pose huge pressure to the integrity of this tropical dry forest, still it have substantial tree species diversity similar to many other dry forests in India and elsewhere.